Comparative field ecology and morphology of two populations of the Troglobitic Catfish Pimelodella Kronei (Siluriformes: Pimelodidae) from Southeastern Brazil - Hoenen, Sônia (Papéis Avulsos de Zoologia, 1997)
This study focused on characterizing the Bombas resurgence population oftroglobitic catfishes Pimelodella kronei from ecological and morphological points of view, and on making comparisons with the previously studied population of V. kronei catfishes from Areias cave. Bombas population ended to be more numerous and with a higher density than Areias population. Considering morphological data, Bombas fishes were smaller than Areias fishes in all parameters measured. On the other hand, values of condition factor for Bombas fishes were higher than those for Areias fishes. Thus, although smaller, they were proportionally heavier. The depigmentation rate of Bombas catfishes was more homogeneous than that of Areias catfishes, being Bombas fishes lighter than Areias fishes in average. Considering ecological and behavioural data, there are some autapomorphies for each population and some similarities which could be eithersynapomorphies or convergences. Thus, either the populations evolved from the same ancestral and nowadays there is a large reduction of genetic flow (and they may have even speciated), or the two populations had different origins. Anyway, there are many evidences to consider them as different species, atleast using thephylogenetic species concept, which should be tested.